The Effect of Using -Based Learning Media Microsoft Sway Office 365 in Learning Geography (In Simple Literature) - Emillia Shandia Dewi; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2020)
The use of ICT-based learning media provides great benefits for the success of the learning process in the classroom. One of the media that is widely used today is Microsoft Sway which is one of the features of Microsoft 365. The use of this media is considered to be quite influential in the learning outcomes of students. This research was conducted to 1) determine the effect of using Microsoft Sway media on students' learning interest in Geography subjects at SMA 2 West Sumatra; 2) determine the effect of using Microsoft Sway media on students' learning creativity in Geography subjects at SMA 2 West Sumatra; and 3) Knowing the effect of using Microsoft Sway media on student learning outcomes in Geography subjects at SMA 2 West Sumatra.